A Shrinking-Core Model for the Degradation of High-Nickel Cathodes (NMC811) in Li-Ion Batteries: Passivation Layer Growth and Oxygen Evolution. Issue 2 (3rd February 2021) - Ghosh, Abir; Foster, Jamie M.; Offer, Gregory; Marinescu, Monica
Abstract : A degradation model for high-nickel positive electrode materials that undergo a structural reorganisation involving oxygen loss and the formation of a disordered (spinel or rock-salt structure) passivation layer is presented for the first time. The model is a thermally coupled continuum model based on the single-particle model and is based upon a LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) layered oxide in this instance. The theoretical framework assumes a shrinking core mechanism, where lattice oxygen, [O], release occurs at the interface between the bulk and the passivation layer, and the rate of reaction is controlled by either [O]-diffusion through the passivation layer or the reaction kinetics at the interface. As the passivation layer grows, the core of active positive electrode material shrinks giving rise to both loss in active material (LAM) and loss in lithium inventory (LLI) through trapping lithium in the passivation layer, giving rise to capacity fade. The slower diffusion of lithium through the passivation layer also gives rise to power fade. The model predicts two limiting cases, " diffusion dominated" if [O]-diffusion is slow, and "reaction dominated" if [O]-diffusion is fast, relative to the reaction rate of [O]-release and also the thickness of the passivation layer.